2015
DOI: 10.1016/j.homp.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Immunological models in high dilution research following M Bastide

Abstract: In 1994, Madeleine Bastide described experimental models in immunology that were used during the 1980s to investigate high dilution effects on several biological systems. She classified the available papers in four categories: High dilutions of antigens; High dilutions of thymus, bursa and other hormones; High dilutions of cytokines; Immunopharmacological activity of silica. The studies about high dilutions of antigens were not continued after this period, but gave rise to a long process of a series of in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
(25 reference statements)
0
14
0
1
Order By: Relevance
“…The effects of homeopathic medicines in relation to the vehicle (placebo) may be seen in studies performed in-vivo or in standard clinical trials. 8,9,[14][15][16][19][20][21][22][23] However, characterizing the specificity of such effects is even more important in refined studies designed in-vitro, 44 since it is known that the succussion itself can promote changes in the solvent organization, including the generation of different oxygenderived radicals, mainly when water is used. [45][46][47] Macrophage cultures are very sensitive for detecting the effect of high dilutions but are also sensitive for detecting such solvent changes as well, concerning elements related to cell oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of homeopathic medicines in relation to the vehicle (placebo) may be seen in studies performed in-vivo or in standard clinical trials. 8,9,[14][15][16][19][20][21][22][23] However, characterizing the specificity of such effects is even more important in refined studies designed in-vitro, 44 since it is known that the succussion itself can promote changes in the solvent organization, including the generation of different oxygenderived radicals, mainly when water is used. [45][46][47] Macrophage cultures are very sensitive for detecting the effect of high dilutions but are also sensitive for detecting such solvent changes as well, concerning elements related to cell oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Using various models of macrophage challenge with other micro-organisms, our team has previously shown that highly diluted medicines, instead of killing the micro-organisms, facilitate the organization of a more effective pattern of macrophage response and arrest the parasite's life cycle. [8][9][10][13][14][15][16][17][18][19][20][21][22][23] For this reason, a similar model was designed herein to explain the clinical results, and avoiding new in-vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Leoni Bonamin reported on the immunological models presented by Madeleine Bastide (deced ee) in 1994. 1 These models on high dilutions of hormones, antigens, cytokines, and then remedy silica have had a considerable influence on follow-up high and UHD research on other models, 8 including the studies with amphibians and thyroid hormone.…”
Section: Part 1 (Biology)mentioning
confidence: 99%
“…2 Leoni Bonamin pays a fitting tribute to Madeleine Bastide, reviewing her work particularly on homoeopathically prepared thymulin which, when administered to mice in the 5CH potency, enhances phagocyte activity in various different experimental situations. 3 Bernard Poitevin looks at other immuno-allergological models. Sadly, the Apis in human basophil degranulation model, which he pioneered with Jacques Benveniste, is among those that have not been replicated.…”
Section: Enduringscientific Fascinationmentioning
confidence: 99%